CASE STUDY OF ENHANCING THE EFFECTIVENESS OF FEMALE ASSOCIATION- AN EXAMPLE OF CHIAYI FEIYAN ENTREPRENEURS ASSOCIATION - Lu, Sho-Min; Lu, Te-Tsai (Graduate Program of Universitas Tarumanagara, 2024)
Women are increasingly assuming vital roles in the domestic industry, with numerous domestic organizations dedicated to assisting women in employment and entrepreneurship. The government has also allocated significant resources for guidance and support. The operational performance of these organizations reflects the tangible benefits of counseling and the influence of women in both the business and social spheres. This study employs qualitative research methods such as